Morphological alterations on the prostate of Calomys callosus submitted to chronic ethanol ingestion - Martinez, M.; Mello, W. [UNESP]; Padovani, C. R. [UNESP]; Martinez, F. E. [UNESP]; Milton, F. A.; De Oliveira, S. A.; Reis, G. S.; Pereira, S. [UNESP]; Segatelli, T. M. [UNESP]; Pinheiro, P. F F [UNESP]; Almeida, C. C D [UNESP]; Cagnon, V. H A (My University, 2006)
The objective of the present study was to assess the possible toxic effects of chronic alcohol ingestion on the ultrastructure of the glandular epithelium of the prostate of the rodent Calomys callosus, in order to contribute to the understanding of the consequences of alcohol abuse for the morphology of the male reproductive apparatus. Sixteen adult animals aged three months were divided into two experimental groups. The control group received a solid diet and tap water, and the alcoholic group received the same solid diet and ethanol P.A. diluted 20% in water (v/v). After 120 days of treatment, all animals were anesthetized, weighed and sacrificed. At the end of treatment, mean body weight did not differ between control and alcoholic animals. The prostate epithelial cells of the alcoholic group showed intense atrophy and ultrastructural alterations such as the presence of lipid droplets, altered nuclei, ruptured mitochondrial cristae, and intense dilatation of the cisterns of the granular endoplasmic reticulum. It was concluded that 20% ethanol provokes marked lesions on the epithelium of the prostate probably interfering on the glandular secretion.
Keywords: Alcohol; Alcoholism; Calomys callosus; Epithelium; Prostate; alcohol; alcoholism; animal; atrophy; body weight; chemically induced disorder; disease model; drug effect; epithelium cell; male; pathology; prostate; rodent; scanning electron microscopy; transmission electron microscopy; ultrastructure; Animals; Atrophy; Body Weight; Disease Models, Animal; Epithelial Cells; Ethanol; Male; Microscopy, Electron, Scanning; Microscopy, Electron, Transmission; Rodentia; Animalia